Targeting FASN enhances cisplatin sensitivity via SLC7A11-mediated ferroptosis in cervical cancer - Xiaojun Wang; Qiqiao Du; Qiuwen Mai; Qiaojian Zou; Shuyi Wang; Xiaoying Lin; Qianrun Chen; Mengxun Wei; Chudan Chi; Zhangqing Peng; Karima Abdugheni; Liu Du; et al. (Translational Oncology)
Objective: The cisplatin resistance significantly hinders the prospects for curing patients with advanced, recurrent, and metastatic cervical cancer (CC). Our study aims to clarify the mechanisms underlying cisplatin resistance in CC and provide a novel treatment strategy to overcome the cisplatin resistance of CC patients. Methods: Intracellular levels of reactive oxygen species, glutathione, malondialdehyde and Fe2+ were measured as indicators of ferroptosis. Biological information analyses, IC50, immunofluorescence assays, qPCR and western blot analyses were conducted to elucidate the functions of FASN in CC. In vivo studies were conducted to examine the antitumor effects of the combination of TVB-2640 and cisplatin. Results: Fatty acid synthase (FASN) was identified as a key driver of cisplatin resistance in CC through transcriptome sequencing and Gene Expression Omnibus (GEO) data analysis. The clinically safe FASN inhibitor TVB-2640 was found to restore cisplatin sensitivity, resulting in synergistic tumor growth attenuation in xenograft models. Mechanistically, FASN downregulation promoted ferroptosis and reduced solute carrier family 7 member 11 (SLC7A11) expression, both in vitro and in vivo models. Conclusion: Targeting FASN enhances cisplatin sensitivity in CC by promoting SLC7A11-mediated ferroptosis. TVB-2640 combined with cisplatin had superior synergistic antitumor effects in cisplatin-resistant CC models.